Adverse selection in the used‐car market: evidence from purchase and repair patterns in the Consumer Expenditure Survey. (March 2014) - Peterson, Jonathan R.; Schneider, Henry S.
<x xml:space="preserve">Abstract</x> We analyze adverse selection in the used‐car market using a new approach that considers a car as an assemblage of parts, some with symmetric information and others with asymmetric information. Using data from the Consumer Expenditure Survey and Consumer Reports, we examine turnover and repair patterns. We find evidence of adverse selection due to the conditions of the transmission, engine, and, during colder months, air‐conditioning; and sorting due to the conditions of the vehicle body and, during warmer months, air‐conditioning. Our quantification exercises indicate that adverse selection may have a meaningful effect on trade volume and quality in the secondhand market.